Validation of the Brazilian 10-item Cervantes Scale for the assessment of menopausal symptoms - Mona Lúcia Dall'Agno; Charles Francisco Ferreira; Fernanda Vargas Ferreira; Pedro do Valle Teichmann; Jéssica Zandoná; Faustino Ramón Pérez-López; Maria Celeste Osório Wender (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To validate the 10-item Cervantes Scale (CS-10) among Brazilian women. Methods: This is a cross-sectional observational study involving women in the community aged 40-55 years in the Southern region of Brazil. They completed a general health, habits and socio-demographic questionnaire, the CS-10 and the Women's Health Questionnaire (WHQ). Women unable to understand the survey, not consenting to participate, or having incapacity imposing difficulties during the completion of the questionnaire were excluded. A Confirmatory Factor Analysis (CFA) was conducted with the AMOS 16.0 software. Chi-square of degrees of freedom (χ2/df), the Comparative Fit Index (CFI), the Tucker-Lewis Index (TLI) and the Root-Mean-Square Error of Approximation (RMSEA) were used as indices of goodness of fit. Cronbach's alpha coefficient was used for internal consistency. Results: A total of 422 women were included (premenopausal n=35, perimenopausal n=172, postmenopausal n=215). The CFA for the CS-10 showed a good fit (χ²/df=1.454, CFI=0.989; TLI=0.985; RMSEA=0.033; CI 90%=0.002-0.052; PCLOSE=0.921; Model p=0.049). Good reliability was established in CS-10 and WHQ (Cronbach's alpha=0.724). Postmenopausal women had higher total CS-10 scores (p≤0.0001), reflecting worse quality of life (QoL) related to menopause symptoms and confirming the greater symptomatology evaluated by high total scores for WHQ found in this population when compared to those in the premenopausal period (p=0.041). Conclusion: The CS-10 is a consistent tool for health-related QoL in Brazilian mid-aged women.